Body image mediates the depressive effects of weight gain in new mothers, particularly for women already obese: evidence from the Norwegian Mother and Child Cohort Study. (December 2016) - Han, Seung-Yong; Brewis, Alexandra; Wutich, Amber
Abstract Background Multiple studies show that obesity and depression tend to cluster in women. An "appearance concern" pathway has been proposed as one basic explanation of why higher weights might lead to depression. The transition to motherhood is a life phase in which women's body image, weight, and depressive risk are in flux, with average weight increasing overall during this period. Examination of how these factors interact from pre- to post-pregnancy provides a means to test how body image plays a key role, as proposed, in causally shaping women's depressive risk. Methods Tracking 39, 915 pregnant women in the Norwegian Mother and Child (MoBA) Cohort Study forward 36 months after their deliveries, we test the moderating and mediating effects of body image concerns on the emergence of new mothers' depressive symptoms by using a binary logistic regression model with a discrete-time event history approach and mediation analysis with bootstrapping. Results For women with high pre-pregnancy body mass index (BMI), weight gain heightens their depressive symptoms over time. Body image concerns mediate the association between weight gain and the development of depressive symptoms regardless of weight status. However, the mediation effect is more evident for women with higher pre-pregnancy BMI. Conversely, better body image is highly protective against the transition to mild or more severe depressive symptoms among new mothers, but only for women who were not classified as obese prior to their pregnancies. Conclusions These findings support a role for body image concerns in the etiology of depressive symptoms during the transition to motherhood. The findings suggest body image interventions before or during pregnancy could help reduce risks of depression in the early postpartum period and well beyond.